From Adam and Israel to the Church : a biblical theology of the people of God - Gladd, Benjamin L., 1978- (Essential studies in biblical theology., 2019)
"This ESBT volume addresses core questions about spiritual identity, examining the nature of the People of God from Genesis to Revelation through the lens of being created and formed in God's image. Benjamin Gladd argues that living out God's image means serving as prophets, priests, and kings, and he explains how God's people function in these roles throughout Scripture"--